Poly(vinyl alcohol)-Based Anion Exchange Membranes for Alkaline Direct Ethanol Fuel Cells - Samsudin, Asep Muhamad; Wolf, Sigrid; Roschger, Michaela; Hacker, Viktor (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Crosslinked anion exchange membranes (AEMs) made from poly(vinyl alcohol) (PVA) as a backbone polymer and different approaches to functional group introduction were prepared by means of solution casting with thermal and chemical crosslinking. Membrane characterization was performed by SEM, FTIR, and thermogravimetric analyses. The performance of AEMs was evaluated by water uptake, swelling degree, ion exchange capacity, OH- conductivity, and single cell tests. A combination of quaternized ammonium poly(vinyl alcohol) (QPVA) and poly(diallyldimethylammonium chloride) (PDDMAC) showed the highest conductivity, water uptake, and swelling among other functional group sources. The AEM with a combined mass ratio of QPVA and PDDMAC of 1:0.5 (QPV/PDD0.5) has the highest hydroxide conductivity of 54.46 mS cm-1. The single fuel cell tests with QPV/PDD0.5 membrane yield the maximum power density and current density of 8.6 mW cm-2 and 47.6 mA cm-2 at 57 Â°C. This study demonstrates that PVA-based AEMs have the potential for alkaline direct ethanol fuel cells (ADEFCs) application.